Quantifying the quality of phytocoenotic classification (theoretical-methodological aspect) (CHORNOMORSKI BOTANICAL JOURNAL, 2016)
This article reviews quantitative approaches to assessing the quality of phytocoenons and phytocoenotic classification. Mathematical criterion is based on calculating phytocoenon’s compactness / distinctness ratio computed from a distance matrix between releves by species composition. Floristic criterion assumes evaluating diagnostic power of species and takes into account total amount of differential species which are classified statistically with fidelity indexes. We also considered related methods which European phytocoenologists applied for the same purpose – among them indexes of sharpness and uniqueness of syntaxon and the Optimclass approach. We measured resemblance of phytocoenotic classifications of the dataset using contingency tables and nominal correlation coefficients. We determined stability of phytocoenons and the robustness of the cluster topology using bootstrapping methods.
Keywords: classification of vegetation, cluster analysis, phytocoenon, classification quality indexes.